SIMILARITIES AND DIFFERENCES IN THE USE OF MODAL WORDS IN UZBEK AND ENGLISH LANGUAGES - Buxarova U. N, Ochilova N. N (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, we examined the intricate and comprehensive category of modality in both the Uzbek and English languages, delving into its unique features and functions. Modality, a linguistic concept that conveys the speaker's attitude towards the likelihood, necessity, permission, or ability related to an action or state, is manifested differently in these two languages.